2020
DOI: 10.1681/asn.2020030276
|View full text |Cite
|
Sign up to set email alerts
|

Renal Involvement and Early Prognosis in Patients with COVID-19 Pneumonia

Abstract: Background Some patients with COVID-19 pneumonia also present with kidney injury, and autopsy findings of patients who died from the illness sometimes show renal damage. However, little is known about the clinical characteristics of kidneyrelated complications, including hematuria, proteinuria, and AKI.Methods In this retrospective, single-center study in China, we analyzed data from electronic medical records of 333 hospitalized patients with COVID-19 pneumonia, including information about clinical, laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

76
752
7
59

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 701 publications
(894 citation statements)
references
References 21 publications
76
752
7
59
Order By: Relevance
“…These results coincide with the reported clinical symptoms of COVID-19, such as loss of taste, loss of olfaction, respiratory dysfunction, and acute nephropathy 16,17 .…”
Section: Discussionsupporting
confidence: 89%
“…These results coincide with the reported clinical symptoms of COVID-19, such as loss of taste, loss of olfaction, respiratory dysfunction, and acute nephropathy 16,17 .…”
Section: Discussionsupporting
confidence: 89%
“…In our cohort, 82.5% of critical SARS-CoV-2 patients presented proteinuria, indicating a high rate of intrinsic kidney injury which is in line with Pei et al concerning the Wuhan pandemic (9). In ICU patients, acute tubular necrosis is well documented up to 78% patients in autopsy series (23) whereas this current population of critically ill SARS-CoV-2 patients presented mixed pattern lesions (23,24).…”
Section: Discussionsupporting
confidence: 88%
“…Another retrospective, multi-center cohort study demonstrated the epidemiological and clinical characteristics of 191 COVID-19 patients, of whom 27 individuals were reported to have AKI, and ten were treated with continuous renal replacement therapy (CRRT) 9 . A brief review of existing papers that reported urology system impairment associated with COVID-19 infection is shown in Table 1 [8][9][10][11][12][13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%